Effects of Hypoxia on Erythrocyte Membrane Properties—Implications for Intravascular Hemolysis and Purinergic Control of Blood Flow - Grygorczyk, Ryszard; Orlov, Sergei N. (Frontiers in Physiology, 2017)
Intravascular hemolysis occurs in hereditary, acquired, and iatrogenic hemolytic conditions but it could be also a normal physiological process contributing to intercellular signaling. New evidence suggests that intravascular hemolysis and the associated release of adenosine triphosphate (ATP) may be an important mechanism for in vivo local purinergic signaling and blood flow regulation during exercise and hypoxia. However, the mechanisms that modulate hypoxia-induced RBC membrane fragility remain unclear. Here, we provide an overview of the role of RBC ATP release in the regulation of vascular tone and prevailing assumptions on the putative release mechanisms. We show importance of intravascular hemolysis as a source of ATP for local purinergic regulation of blood flow and discuss processes that regulate membrane propensity to rupture under stress and hypoxia.